Hubungan dukungan instrumental dengan beban pada anggota keluarga skizofrenia di Poliklinik Keperawatan Jiwa RSJ Grhasia Provinsi DIY - Rohana Fatma Zahra; Sutejo Sutejo (Caring : Jurnal Keperawatan, 2019)
Schizophrenia is a set of some clinical indications shown by cognitive disorder, emotional disorder, perceptional and behavioural disorder. Schizophrenia does not only attack psychologically but also affects one’s social and economic condition. One of the social supports from family is instrumental support as economic function and health treatment given by a family member. Schizophrenia does not directly cause death, but it will make the patient unproductive and become the family burden. Family is the smallest unit of society consisting of the head of the family and some people under the same roof who depends on each other. This research objective is to find out the correlation between instrumental support and burden of schizophrenia family members at Mental Treatment Polyclinic of Grhasia Mental Hospital, Yogyakarta Special Province The design of this research is non-experimental correlation using cross-sectional design, while the sampling of the technique was using accidental sampling. The samples of the research consist of the 91 family members of schizophrenia patients at Grhasia Mental Hospital of Jogjakarta Special Province. The data were collected using a questionnaire and then tested statistically using Spearman’s correlation. Most of the family instrumental support is in high category (76.1%), and the burden of the family members of schizophrenia patients is also high (54.9%). The analysis result shows that there is no significant correlation between instrumental support and burden of family members (p-value = 0.820). There is no correlation between instrumental support and burden among the family members of schizophrenia patients at Mental Treatment Polyclinic of Grhasia Hospital Yogyakarta Special Province. It is suggested that the family members of the patients can accept patients well through patient treatment involving all family members, not only caregivers.